(untitled) (Heritage, 2023)
The problem of literature as a critique of ideology is essentially a question of the relationship between creativity and artistic freedom, on the one hand, and social order, on the other. With Predrag Palavestra (1930–2014), this question is a continuation of the discussion about critical literature as an alternative to postmodernism and its development trends. The book of essays Literature - Critique of Ideology (1991) contains 17 papers and all of them stem from the book Critical Literature (1983) in which 31 papers were printed. The introductory place in the discussion of literature as a critique of ideology belongs to the problem of Serbian literature in the Yugoslav or South Slavic civilization at the moment when it became clear that the Yugoslav state was falling apart. Palavestra starts from the idea, even though since the time when its concept was defined (as an ideological and state goal), Yugoslav civilization remained an imaginary concept, that the first task of Serbian intellectuals at that time was to "bring and establish a new, modern, critical and democratic Serbian national program", based on experience in the past and present, so the Yugoslav civilization will survive, if other intellectual forces of the Yugoslav peoples decide for it "democratically and with creative energies, truly and actively". The task of the work is to show how Palavestra’s critical thought, communicated throughout the world, aimed to understand the values ​​not only of Serbian literature and culture, but also to prevent the drama and bloody disintegration of the Yugoslav state and the civil war of its peoples. In all parts of the world, in many institutions, newspapers and magazines, he advocated dialogue as a way out of impasse. Also, we show that all the books and topics he dealt with were the way to the great synthesis he achieved in the History of Serbian Literary Criticism 1768 – 2007 (2008).